Engineering properties of leucaena leucocephala for prevention of slope failure - Normaniza, O.A.; Barakbah, S.S.; Faisal, H. (2008)
The potential of Leucaena leucocephala as an erosion control plant was investigated in terms of its capacity of root reinforcement, root profile and root shear strength. The species studied exhibited extensive, dense rooting and depth of penetration. These aspects, to some extent, could provide surficial as well as deep-seated erosion control. A high water absorption capacity would increase suction, thus potentially extracting water at the greater depth. The soil-root matrix significantly affects cohesion factor but not the angle of friction. The effect varies with increasing depth and age of plant depending on the root length density. After 6 months of growth, the cohesion factor had tremendously increased by two- to five-fold (0.1-0.5 m soil depth). This range almost reached the values of those in the 12-month treatment, indicating a high contribution of the root system to soil-root reinforcement. (C) 2007 Elsevier B.V. All rights reserved.